Draft genome of ochrobactrum intermedium strain M86 isolated from non-ulcer dyspeptic individual from India - Kulkarni, Girish; Dhotre, Dhiraj; Dharne, Mahesh S.; Shetty, Sudarshan; Chowdhury, Somak; Misra, Vatsala; Misra, Sriprakash; Patole, Milind; Shouche, Yogesh (GUT Pathogens, 2013)
Background: Ochrobactrum intermedium is an emerging opportunistic pathogen of humans that is closely related to members of the genus Brucella. Earlier, we reported the case of an Indian subject with non-ulcer dyspeptic symptoms whose urease positive gastric biopsy revealed the presence of Helicobacter pylori along with non-Helicobacter like bacteria, eventually cultured and identified as O. intermedium strain M86. Results: Here, we describe the unclosed draft genome of the strain M86 with a length of 5,188,688 bp and mean G+C content of 57.9%. We have also identified many putative gene clusters that might be responsible for its persistence in the gastric mucosa. Comparative analysis of genomic features of Ochrobactrum intermedium strain M86 and Ochrobactrum intermedium LMG 3301(T) was also done. Conclusions: This paper attempts to gain whole-genome based insights into the putative gene determinants of O. intermedium for survival in the highly acidic stomach lumen environment. Identification of genes putatively involved in the various metabolic pathways may lead to a better understanding of the survival of O. intermdedium in acidic condition.

Bacterial communities and diversity of western ghats soil: a study of a biodiversity hotspot - Ghare, Uma; Narvekar, Simran; Lodha, Tushar; Mallebhari, Rubiya; Dastager, Syed; Barvkar, Vitthal T.; Dhotre, Dhiraj; Karmalkar, Nitin R.; Pable, Anupama A. (Current Microbiology, 2023)
The Western Ghats is one of India's mega-diversity hotspots and an ecologically and geologically important area for the diversity of endemic plants and animals. The present study provides insights into the aerobic bacterial diversity and composition of the soils of North Western Ghats located in Maharashtra state (NWGM), India. The samples for the culture-dependent study were collected from 6 different locations namely Malshej Ghat, Bhimashankar, Lonavala, Mulshi, Tail-Baila, and Mahabaleshwar. A total of 173 isolates were obtained from the different samples, which belonged to Proteobacteria (43%), Firmicutes (36%), and Actinobacteria (19%). Sequences of 15 strains shared <= 98.7% similarity (a species cut-off) which represent potential novel species. Metagenomic analysis revealed the presence of Actinobacteria and Proteobacteria as the most dominant phyla at both MB and MG. However, both sites showed variation in the composition of rare phyla and other dominant phyla. This difference in bacterial community composition could be due to differences in altitude or other physicochemical properties. The functional prediction from the amplicon sequencing showed the abundance of carbohydrate, protein, and lipid metabolism which was corroborated by screening the isolated bacterial strains for the same. The present study has a unique take on microbial diversity and defines the importance of community assembly processes such as drift, dispersal, and selection. Such processes are relatively important in controlling community diversity, distribution, as well as succession. This study has shown that the microbial community of NWGM is a rich source of polysaccharide degrading bacteria having biotechnological potential.